PENGARUH PUPUK MULTI KP DAN LAMA PENYIMPANAN MATA ENTRES TERHADAP PERTUMBUHAN OKULASI JERUK MANIS (Citrus nobilis L.) - Restu Hadi Syahendra; T. Edy Sabli (DINAMIKA PERTANIAN, 2024)
This study determines the impact of the interaction between Multi KP fertilizer and the duration of scion storage on the growth of sweet orange grafts. The research was conducted at the Experimental Farm of the Faculty of Agriculture at the Islamic University of Riau, located at Jalan Kaharudin Nasution No: 113, Air Cool Village, Bukit Raya District, Pekanbaru. The study spanned three months, from April to June 2022. A Factorial Completely Randomized Design (CRD) was implemented, featuring two primary factors. The first factor was Multi KP Fertilizer, tested at four levels: 0, 2, 4, and 6 grams per plant. The second factor concerned the duration of scion storage, also with four levels: 0, 2, 4, and 6 days. This design resulted in 16 treatment combinations, each replicated three times, totaling 48 plots. From each plot, four plants were grown, and two plants were sampled, resulting in a total of 192 plants for analysis. The findings indicate that the interaction between KP fertilizer and scion storage time significantly influenced all observation parameters. The optimal treatment involved a fertilizer dosage of 6 grams per plant combined with a storage duration of 6 days. Additionally, KP fertilizer alone had a notable positive effect on all observed parameters, with the best results again corresponding to the 6 g/plant dosage. The duration of scion storage also had significant effects across all measured parameters, with the most beneficial duration being 6 days.